From climate knowledge to collective action: the case for integrating sustainability science and strategic communication as a catalyst for change - Martin, Christopher; Pira, Hannah (Frontiers in Sustainability, 2025)
The sustainability value-action gap remains a critical challenge. In this perspective, we argue that, without structural institutional change, current scientific communication methods will fail to drive systemic transformation at the necessary scale and speed. We therefore advocate for the integration of strategic communications, drawing insights from marketing and advertising to enhance the effectiveness of sustainability messaging. We outline three principles for this shift: fostering emotionally resonant and value-aligned associations, balancing long-term messaging with short-term appeals, and tailoring messages to the lived experiences of target audiences. Real-world examples, ranging from climate adaptation in King County to narrative campaigns in New York, demonstrate the potential of these approaches. We conclude by advocating for building strategic communication capacity, the development of boundary spanning professionals, and a call for greater institutional recognition of communication as a professional practice essential to sustainability transformation.